Analisis Efektivitas Pemungutan Pajak Bumi Dan Bangunan (PBB) Dan Kontribusinya Pada Pendapatan Daerah Kabupaten Sikka Tahun 2018-2023 - Maria Susanti; Andreas Rengga; Petrus Dasilva (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2025)
This study aimed to determine the (1) effectiveness of Land and Building Tax (PBB) collection and (2) its contribution to Local Revenue (PAD) of Sikka Regency. The approach used in this research was descriptive quantitative. Data collection techniques included observation, interviews, documentation, library research, and internet-based research. The study was conducted at the Regional Revenue Agency of Sikka Regency. The research results indicated that, overall, the effectiveness of Land and Building Tax (PBB) collection was considered moderately effective, with an average percentage of 85.99%. However, the contribution of the Land and Building Tax to Local Revenue (PAD) was assessed as very low, with a percentage of 4.17%.